Exercise training as prophylactic strategy in the management of neutropenia during chemotherapy. (20th June 2020) - Schauer, Tim; Hojman, Pernille; Gehl, Julie; Christensen, Jesper Frank
Abstract : Chemotherapy‐induced immune‐suppression is a common, but potential detrimental, adverse reaction in patients undergoing treatment for cancer and strategies with capacity to boost the immune cell populations are needed. Physical exercise training is a potent regulator of immune cell viability and function and may serve as a viable, non‐pharmacological prophylactic strategy in addition to the current pharmacological management by, for example, granulocyte‐colony stimulating factor (G‐CSF). Here, we review the mechanistic evidence linking exercise training to haematopoietic function and subsequent possible amelioration of chemotherapy‐related neutropenia. First, we briefly describe neutrophil regulation and management of neutropenia in cancer patients. Second, we summarize the effect of acute and chronic exercise training on neutrophils and their progenitors, and finally, we outline the current clinical evidence of exercise interventions in ongoing anti‐cancer treatment in regard to neutropenia incidence, treatment tolerance and related outcomes. LINKED ARTICLES: This article is part of a themed issue on New avenues in cancer prevention and treatment (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.12/issuetoc